Nitrate removal potential of Rhodobacter sphaeroides isolated from Abattoir wastewater of Gombe Township, North-eastern Nigeria - Saidu, Haruna; Muhammed, Kabiru; Muhammed Abba, Ishaku; Magaji, Buhari (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Nitrogen is one of the essential nutrients in ecosystem but its accumulation could results into the generation of wastewater and also affects nitrogen cycle. This means that, employment of denitrifying bacteria for treatment is needed to protect our environment. In this study, a denitrifying photosynthetic bacterium capable of nitrate removal was isolated using serial dilution and streak plating method and was characterized using morphological, biochemical and physiological methods. The isolate was found to show spherical patches of red coloration detected at 300 and 1100nm respectively using ultraviolet spectrophometer. The isolate was also found to respond positively to oxidase, urease, catalase, citrate, malate, ethanol and glucose test with a strong physiological potential of growing under anaerobic-light and dark condition but could not thrive under aerobic light and dark condition. The active growth of the isolate was detected between days 0-1, followed by stationary phase and then decline phase. The highest biomass concentration of 4.1 mg/L was produced at day 7 culture under 85 mg/L whereas the lowest was detected at 320 mg/L of 1.3 mg/L at day 6. The effect of various initial concentration of the nitrates (85, 135, 190, 235, 290 and 320 mg/L) were measured on the rate of nitrate removal. At 85 mg/L, highest nitrate removal of 88% without accumulation was achieved, followed by 81, 77, 73, 67, 60 % at 135, 190, 235, 290 and 320 mg/L respectively. The results showed that increase in concentration resulted into the decrease in nitrate removal. Thus, this strain can serves as good for use in wastewater treatment plan.